Pengaruh Literasi Ekonomi dan Gaya Hidup terhadap Perilaku Konsumtif Mahasiswa Angkatan 2021 Jurusan Pendidikan Ekonomi - Isma A. Latif; Radia Hafid; Ardiansyah Ardiansyah; Meyiko Panigoro; Agil Bahsoan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine the effect of economic literacy and lifestyle on the consumptive behavior of 2021 cohort students in the Economics Education Department, Faculty of Economics and Business, State University of Gorontalo. This research is motivated by the increasing tendency of consumptive behavior among students, which is influenced by easy access to information and modern lifestyles. The type of research used is quantitative research with primary data sources obtained through questionnaires distributed to 35 respondents. The data analysis technique uses multiple linear regression with the help of statistical software. The results show that the variables of economic literacy and lifestyle simultaneously have a significant effect on students' consumptive behavior. The contribution of these two variables is 0.406 or 40.6%, while the remaining 59.4% is influenced by other factors outside this research model.These findings are expected to serve as a consideration for students to be wiser in managing their finances and forming a rational lifestyle, as well as to increase awareness of the importance of personal financial planning for a more stable and sustainable future well-being in today's modern social and economic environment.